2015
DOI: 10.1186/s40810-014-0002-4
|View full text |Cite
|
Sign up to set email alerts
|

An acute dose, randomized trial of the effects of CDP-Choline on Mismatch Negativity (MMN) in healthy volunteers stratified by deviance detection level

Abstract: Background: Alpha 7 nicotinic acetylcholine receptors (α7 nAChR) are prioritized molecular targets for the development of new pharmacological treatments for impaired cognition in schizophrenia. The use of schizophrenia-associated biomarkers both as endpoints and for segmentation of homogeneous populations for early detection of cognitive enhancing agents has been advanced to enhance the drug discovery process. Methods: In this study, the mismatch negativity (MMN) event-related brain potential (ERP), considered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
18
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 167 publications
(175 reference statements)
8
18
0
1
Order By: Relevance
“…Another possibility is that nicotinic effects were influenced by differences baseline MMN; nicotine increases MMN amplitude in healthy subjects with low baseline MMN but has the opposite effect in healthy subjects with high baseline MMN (Knott et al, 2014a). In line with these findings, a similar pattern of baseline dependence was observed in healthy subjects given an acute dose of choline (Knott et al, 2015). All three patient studies also had relatively low sample sizes ( n = 10–12) and the effects of nicotine on MMN in schizophrenia are therefore inconclusive.…”
Section: Later Waveforms: the Mismatch Negativity And P300supporting
confidence: 80%
“…Another possibility is that nicotinic effects were influenced by differences baseline MMN; nicotine increases MMN amplitude in healthy subjects with low baseline MMN but has the opposite effect in healthy subjects with high baseline MMN (Knott et al, 2014a). In line with these findings, a similar pattern of baseline dependence was observed in healthy subjects given an acute dose of choline (Knott et al, 2015). All three patient studies also had relatively low sample sizes ( n = 10–12) and the effects of nicotine on MMN in schizophrenia are therefore inconclusive.…”
Section: Later Waveforms: the Mismatch Negativity And P300supporting
confidence: 80%
“…With respect to drug interactions, adolescent exposure to nicotine has been found to modify acute functional response to cannabinoid agonists in rats (Viveros et al, 2006) and chronic nicotine use has been shown to mask disruptions in cognitive neurocircuitry associated with adolescent cannabis use (Jacobsen et al, 2007). Cannabidol, a non-psychoactive ingredient of the cannabis plant has been shown to inhibit the function of the α7 nicotinic acetylcholine receptor (Mahgoub et al, 2013), which is diminished in numbers in SZ (Freedman et al, 2000) and when stimulated with a selective agonist has resulted in increased sensory memory in healthy individuals with low MMN amplitudes (Knott et al, 2015).…”
Section: Introductionmentioning
confidence: 98%
“…In contrast, Christensen et al () showed that repeated administration of A‐582941, an α7 nAChR agonist, with no positive allosteric modulator, increases α7 nAChR levels in several brain regions (especially prefrontal cortex). It is also suggested that, nAChR agonist effects display an inverted U‐shaped dose response curve, with maximal effects being observed at low and ultralow doses (Knott et al, ). Relatively high dose citicoline was utilized in this study and fairly satisfactory results were gained.…”
Section: Discussionmentioning
confidence: 99%
“…Relatively high dose citicoline was utilized in this study and fairly satisfactory results were gained. Nonetheless, it is not clear whether this high dose has reduced the actual nAChR agonist effect (Knott et al, ).…”
Section: Discussionmentioning
confidence: 99%